Organodiselenides: Organic Catalysis and Drug Design Learning from Glutathione Peroxidase - Tiezza, Marco D.; Ribaudo, Giovanni; Orian, Laura (Current Organic Chemistry, 2019)
Organodiselenides are an important class of compounds characterized by the presence of two adjacent covalently bonded selenium nuclei. Among them, diaryldiselenides and their parent compound diphenyl diselenide attract continuing interest in chemistry as well as in close disciplines like medicinal chemistry, pharmacology and biochemistry. A search in SCOPUS database has revealed that in the last three years 105 papers have been published on the archetypal diphenyl diselenide and its use in organic catalysis and drug tests. The reactivity of the Se-Se bond and the redox properties of selenium make diselenides efficient catalysts for numerous organic reactions, such as Bayer- Villiger oxidations of aldehydes/ketones, epoxidations of alkenes, oxidations of alcohols and nitrogen containing compounds. In addition, organodiselenides might find application as mimics of glutathione peroxidase (GPx), a family of enzymes, which, besides performing other functions, regulate the peroxide tone in the cells and control the oxidative stress level. In this review, the essential synthetic and reactivity aspects of organoselenides are collected and rationalized using the results of accurate computational studies, which have been carried out mainly in the last two decades. The results obtained in silico provide a clear explanation of the anti-oxidant activity of organodiselenides and more in general of their ability to reduce hydroperoxides. At the same time, they are useful to gain insight into some aspects of the enzymatic activity of the GPx, inspiring novel elements for rational catalyst and drug design.
Keywords: antioxidants